FINANCIAL ANALYSIS OF BROILER CHICKEN FARMING BUSINESSES IN THE SANTRI EMPOWERMENT PROGRAM IN LANGKAT DISTRICT - Murni Park; Muhammad Buhari Sibuea; Tumpal HS Siregar (CV. Radja Publika, 2024)
Funding is one of the biggest problems facing small-scale broiler chicken farmers. Another problem is not knowing how to cultivate it properly and the difficulties in selling it. Partnerships are one way to overcome the challenges commonly faced by boiler chicken farmers. PT. Charoen Pokphand and Pesantren Darussalaam, who run a boiler chicken farming operation in Langkat, North Sumatra Province, use the partnership model. The purpose of this study is to calculate the financial feasibility of the program using the benefit cost ratio (BCR), net present value (NPV), internal rate of return (IRR), and payback period (PP). Additionally, to determine how changes in labor expenses and feed prices may affect farmers' revenue. With a purposive sampling method, this explanatory research uses a case study strategy. The results of the financial analysis found that Darusalam Islamic Boarding School boiler chicken farming business was feasible, as indicated by the net present value (NPV) of IDR 316,719,165, benefit cost ratio (BCR) of 1.74, internal rate of return (IRR) of 25%, and payback period (PP) of 1.93 years. The results of the sensitivity analysis have the most sensitive changes to the business in the form of increased feed costs. Partnership system broiler farmers like Darussalam Islamic Boarding School cannot regulate selling and feed prices, so the only way to keep the business viable is to maintain the resulting production. Therefore, Farmers must be able to master cage management and good production management in order to produce maximum broiler chicken production